Meningkatkan Penjualan Produk Menggunakan Blogger Pada UMKM Gabin Fla Susu MS.SR di Kota Padang - Elsa R. Sigalingging; Ziza Fazira; Susan Olivia; Sularno; Rafidola Mareta Riesa (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Currently, technology and information have developed and everything is digital, of course this also has an impact in the business world, so business owners must be able to keep up with technological developments and utilize them effectively so that business products are better known. Many media can be used to promote business products, one of which is Blogger. This research is a blog design for UMKM Gabin Fla Susu MS. SR, this Project Base Learning (PBL) program is a form of realization of the Web Design Course. The goal is to help MSME businesses to market their products, increase sales and product popularity through bloggers. In this study, the methods used were observation and interviews with business owners before a blog was created for MS.SR Gabin Fla Susu MS.